JHEA, Volume 12, n°2, 2014 - Full Issue - journal system, (Journal of Higher Education in Africa, 2014)
Contents The Shifting Landscape of Development Cooperation: Repercussions for African Higher Education Damtew Teferra ................................................1 Universities and Regional Development: Lessons from the OECD Regional Assessment of the Free State, South Africa Samuel Fongwa, Lochner Marais & Doreen Atkinson.........................29 African Languages Policy in Education of South Africa: 20 Years of Freedom or Subjugation? Neo Lekgotla laga Ramoupi.........................53 Revitalising Higher Education for Africa’s Future Ebrima Sall & Ibrahim Oanda.......................95 Neoliberalism and the Changing Role of Universities in Sub-Saharan Africa: The Case of Research and Development Daniel N. Sifuna .................................109 Quality Assurance in Ethiopian Higher Education: Boon or Bandwagon in Light of Quality Improvement? Tefera Tadesse ............................131